How Are Interbank and Sovereign Debt Markets Linked? Evidence from 14 OECD Countries, the Euro Area and Russia - Stolbov, Mikhail (Panoeconomicus, 2014)
The paper explores causal linkages between interbank and sovereign bond markets in 14 OECD countries, the Euro area and Russia during the 2008-2009 crisis and post-crisis period. The analysis has been carried out for individual countries and in a multivariate framework. It enables to identify systemically important countries in both markets. The USA, Switzerland, Australia, South Korea and Russia are of particular significance in the interbank lending market. Switzerland, the UK, Poland, Australia and Canada play a pivotal role in the public debt market. The analysis under the multivariate framework reveals substantial heterogeneity in the network structure of both markets. Only 12% of causal relationships coincide, which may fuel financial contagion. Volatility spillovers underlie the causal linkages. They are estimated by means of dynamic volatility indices based on rolling correlation matrices and help identify the transformation of the international banking turmoil into the sovereign debt crisis. Key words: Interbank lending markets, Public debt, Granger causality, Diks-Panchenko test, Rolling correlations. JEL: G17, G21, H6.